2014
DOI: 10.1016/j.mimet.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a disposable amperometric magneto-genosensor for the detection and identification of Streptococcus pneumoniae

Abstract: A disposable PCR-based amperometric magneto-genosensor for detection and identification of Streptococcus pneumoniae was evaluated. ROC curve analysis used to determine optimal signal cutoff values yielded a sensitivity of 91% and a specificity of 90%. The method was also tested for the direct detection of pneumococci in clinical samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In particular, genosensors based on magnetic microbeads and PCR amplification, have been broadly used in clinical applications and food analysis because of their excellent sensitivity, reproducibility, reduced time of analysis, high sample throughput and easy automation with minimum consumption of the sample and reagents [39,40]. To the best of our knowledge, only a few genosensors, mainly microarrays, have been developed for fungal pathogen screening and identification.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, genosensors based on magnetic microbeads and PCR amplification, have been broadly used in clinical applications and food analysis because of their excellent sensitivity, reproducibility, reduced time of analysis, high sample throughput and easy automation with minimum consumption of the sample and reagents [39,40]. To the best of our knowledge, only a few genosensors, mainly microarrays, have been developed for fungal pathogen screening and identification.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, it is worth to mention that very recently the Lobo-Castañón’s research group has reported, for the first time, the use of on-surface helicase-dependent amplification at ITO surfaces to quantify electrochemically very small amounts of genomic DNA extracted from Salmonella [ 31 ]. Attractive electrochemical nucleic acid sensors have been reported so far for non-invasive bacterial infections detection coupled with PCR [ 32 , 33 , 34 ], HDA [ 25 , 31 , 34 ], RPA [ 35 ] and HCR [ 36 ].…”
Section: Electrochemical Affinity Biosensing Of Infectious Pathogementioning
confidence: 99%
“…Furthermore, this methodology demonstrated a clear discrimination against Streptococcus mitis (a closely related streptococcus) and between blood and urine samples non-inoculated and inoculated with the target bacteria at a very low concentration (10 3 CFUs mL −1 ). The DNA sensor was successfully validated with 109 clinical samples of diverse origins providing both sensitivity and specificity of around 90% [55]. …”
Section: Electrochemical Genosensing Of Circulating Biomarkersmentioning
confidence: 99%